انجاز الحاجہ شرح سنن ابن ماجہ کا منہج واسلوب، تحقیقی جائزہ: Methodology of Injaz ul Hajah Sharah Sunan Ibn e Majah A Research View - Hafiz Abdullah Saleem; Dr Hafiz Qudratullah (International Research Journal of Arabic and Islamic Studies, 2024)
Every author sets some principles and guidelines in their work, according to which they shape their research and writing; in fact, that becomes their methodology and style. While explaining Sunan Ibn Majah, the methodology adopted by the commentator of Hadith, Sheikh al-Hadith Maulana Muhammad Ali Janbaz, for the explanation and clarification of difficult words in the Hadith is based on the following key points: The commentator has utilized books on the difficult words of Hadith to resolve the unusual aspects of Hadith. He has compared other editions of the book, which helps in identifying the meanings. The meanings of words in Arabic, Persian, and Urdu have been clarified. By compiling various texts, he has presented explanations of the meanings. He has benefited from the scholars of language to make it easier to solve difficult Arabic words. He has also explained the reasons for the diacritics concerning Arabic grammar. He has clarified confusion by accurately identifying the correct locations among similar names.The following aspects have been given importance for clarifying the meaning of Hadith: He frequently explained the title of Hadith (Tarjamah al-Bab). He referenced Quranic verses to support the explanation and evidence of the Hadith. He received valuable guidance from the sayings of the Sahabah and the Tabi‘in.The controversial issues between the scholars of the Ummah and the great jurists have been described with great politeness and respect. He made extensive use of the books and commentaries of the early scholars. There is a detailed discussion on the periods of trials (fitnah) and guidance about them, as well as an identification of the fitans. The introduction of false and misguided sects, such as the Mu'tazila, Jahmiyyah, Imāmiyyah, and other misguided sects has been provided, and a refutation of them has also been presented.